Assessing the quality of bovine embryos produced in vitro through the inner cell mass and trophectoderm ratio - Maylem, Excel Rio S.; Leoveras, Ma. Elizabeth DC; Atabay, Edwin C.; Atabay, Eufrocina P. (2017)
Embryo quality and implantation potential are the most important factors influencing the rate of successful pregnancies. These two are related to the occurrence of the three morphogenetic process (i.e., compaction, blastulation, and hatching) and the allocation of embryonic cells to the inner cell mass (ICM) and trophectoderm (TE) in response to proper timing of embryonic development. This research was conducted to determine the allocation of ICM and TE of bovine embryos in vitro in relation to its developmental stage and age. The account of this event can be used as benchmark for comparison of good quality embryos for transfer. Using a defined medium ? modified synthetic oviductal fluid for IVC ? 85 bovine embryos derived from the slaughter house were assessed for cell number and ICM and TE ratio using the Hoechst 33342-propidium iodide differential staining method. Embryos collected on days 7, 8, and 9 were stained, viewed, and examined using fluorescence microscope and Nikon Imaging Software - Basic Research. The results revealed that in terms of total cell number (mean ± SD), the expanded blastocyst on the 7th day (109.29 ± 41.09) and hatched blastocyst on the 8th day (139.5 ± 43.13) yielded the highest total cell number. From these two stages, chi square test determined that the 7th day expanded blastocyst with an ICM:TE count (ratio) of [34.4 ± 15.4]:[73.2 ± 34.9] (0.47) fits to the 1:3 ratio given for a good quality embryo. The results of the present study indicate that the 7th day expanded bovine blastocyst developmental stage and age has the highest potential for pregnancy when transferred owing to its being able to achieve the desired cell number and ICM and TE. (Author's abstract)